DEEP REPOSITORY FOR SPENT NUCLEAR FUEL - Gašper Žerovnik; Luka Snoj; Matjaž Ravnik; Marjan Kromar (Journal of Energy Technology, 2024)
In spite of the possibility of fuel reprocessing, direct spent nuclear fuel disposal is still a viable option in Slovenia. The current strategy regarded by Slovenian Agency for Radwaste Management is terminal disposal in deep repository. Due to decay heat release, spent nuclear fuel interacts with the repository site and the surrounding rock. Arrangement of spent fuel in the repository according to its decay heat was demonstrated for the case of the Krško Nuclear Power Plant.